Fat Grafts Augmented With Vitamin E Improve Volume Retention and Radiation-Induced Fibrosis. (29th March 2022) - Abbas, Darren B; Lavin, Christopher V; Fahy, Evan J; Griffin, Michelle; Guardino, Nicholas J; Nazerali, Rahim S; Nguyen, Dung H; Momeni, Arash; Longaker, Michael T; Wan, Derrick C
Abstract: Background: Treatments for radiation-induced fibrosis range from vitamin E (VE) and pentoxifylline (PTX) systemically to deferoxamine and fat grafting locally. Regarding fat grafting, volume retention hinders its long-term functionality and is affected by 2 factors: inflammation and necrosis secondary to hypovascularity. Objective: The authors aimed to simultaneously improve fat graft retention and radiation-induced fibrosis by integrating VE and PTX into fat grafts locally. Methods: Forty adult CD-1 nude male mice, 6 weeks old, underwent scalp irradiation and recovered for 4 weeks to allow for development of fibrosis. Mice received 200 μL of donor human fat graft to the scalp. Mice were separated into 4 conditions: no grafting, fat graft without treatment, graft treated with PTX, and graft treated with VE. Fat graft volume retention was monitored in vivo with micro-computed tomography scans at weeks 0, 1, 2, 4, 6, and 8 after grafting. Histological and cytokine analysis of the scalp skin and fat grafts were performed. Results: VE-treated grafts had significant improvement in dermal thickness and collagen density of overlying skin compared with all other groups. VE decreased 8-isoprostane and increased CD31 +  staining compared with the other grafted groups. Cytokine analysis revealed decreased inflammatory and increased angiogenic markers in both the fat graft and overlying skin of the VE group. Fat graft volume retention was significantly improved in the VE group starting at 1 week post grafting. Conclusions: Radiation-induced fibrosis and fat graft volume retention are both simultaneously improved with local administration of VE.